Sosialisasi Peduli Lingkungan Melalui Pembuatan Pupuk Organik Cair (POC) di SMP Negeri 18 Bengkulu Utara, Kecamatan Enggano - Zakhi Restu Pratama; Sania Dewi Kusuma Ningrum; Devi Anggraini; Sarfraj Yulia Rohan; Yopiko Tri Delta (Yayasan Darussalam Bengkulu, 2025)
This community service activity aims to enhance the awareness and skills of students at SMP Negeri 18 Bengkulu Utara, Enggano Island, in organic waste management through the production of liquid organic fertilizer (POC). The main issue underlying this activity is the low understanding among the younger generation regarding organic waste management and local farmers' dependence on synthetic chemical fertilizers. The method employed was participatory action learning, comprising theoretical socialization, demonstration, and direct practice over two days. A total of 30 students were divided into small groups to practice making POC using local organic waste, rice washing water, molasses, and EM4 as a fermentation starter. The results showed a significant increase in students' understanding of organic waste recycling and environmentally friendly agriculture, measured through observation and participant reflection. Additionally, a commitment was formed among students to continue the independent practice of POC production. This activity contributes to strengthening environmental literacy among young generations in remote island areas while supporting sustainable agricultural achievements on Enggano Island